I want to solve for the asymptotic solution of the following differential equation

$$ \left(y^2+1\right) R''(y)+y\left(2-q \left(b \sqrt{y^2+1}\right)^{-q}\right) R'(y)-l (l+1) R(y)=0$$

as $y\rightarrow \infty$, where $q>0$. I did the standard way by obtaining a series solution by the Frobenius method prescription in the form

$$R(y)=\sum_{n=0}^\infty \frac{a_{n}}{y^{n+k}}$$ where $k=l+1$ is the indicial exponent. I had difficulty finding for a recurrence relation for the coefficients $a_n$ for arbitrary value of the parameter $q$. Right now, I am just doing the brute force method of solving individual $a_n$ for every value of $q$. But I am just wondering whether the recurrence relation is possible to solve. Can this be solved analytically?

  • $\begingroup$ It would help if you provide the recurrence relation you obtained $\endgroup$ – Yuriy S Aug 4 at 16:10
  • $\begingroup$ I think you are supposed to use $y^2+1 \to y^2$ as $y \to \infty$, which should make for a nice explicit recurrence relation once you substitute the Frobenius series $\endgroup$ – Yuriy S Aug 4 at 16:43
  • $\begingroup$ I havent solved yet the recurrence relation. Can it be solved? $\endgroup$ – user583893 Aug 5 at 0:12
  • $\begingroup$ My problem is how to get rid with $q$. I dont know what to do $\endgroup$ – user583893 Aug 5 at 2:48
  • $\begingroup$ Is $q$ an integer? If it's an integer, then I know what to do. If it's not an integer, the problem gets more complicated $\endgroup$ – Yuriy S Aug 5 at 8:15

First, we take the most complicated term and expand it in a series around $y \to \infty$:

$$\left(\sqrt{y^2+1}\right)^{-q}= \frac{1}{y^q} {_2 F_1} \left(\frac{q}{2},1;1;-\frac{1}{y^2} \right)= \sum_{k=0}^\infty \frac{(-1)^k (q/2)_k}{k!} \frac{1}{y^{2k+q}}$$

Where $(p)_k=p(p+1)(p+2) \cdots (p+k-1)$ is the Pochhammer symbol, and I'm using hypergeometric series instead of binomial series because it's more convenient.

Then we divide the equation by $y^2$ and obtain:

$$\left(1+\frac{1}{y^2}\right) R''(y)+\left(\frac{2}{y}-\frac{q}{b^q} \sum_{k=0}^\infty \frac{(-1)^k (q/2)_k}{k!} \frac{1}{y^{2k+q+1}} \right) R'(y)-\frac{l (l+1)}{y^2} R(y)=0$$

Now substitute:

$$R(y)=\sum_{n=0}^\infty \frac{a_{n}}{y^{n+\alpha}} \\ R'(y)=-\sum_{n=0}^\infty \frac{(n+\alpha) a_{n}}{y^{n+\alpha+1}} \\ R''(y)=\sum_{n=0}^\infty \frac{(n+\alpha)(n+\alpha+1) a_{n}}{y^{n+\alpha+2}}$$

We obtain:

$$\sum_{n=0}^\infty \frac{(n+\alpha)(n+\alpha+1) a_{n}}{y^{n+\alpha+2}}+\sum_{n=0}^\infty \frac{(n+\alpha)(n+\alpha+1) a_{n}}{y^{n+\alpha+4}}-2\sum_{n=0}^\infty \frac{(n+\alpha) a_{n}}{y^{n+\alpha+2}}+ \\ + \frac{q}{b^q} \sum_{n=0}^\infty \sum_{k=0}^\infty \frac{(-1)^k (q/2)_k}{k!} \frac{(n+\alpha) a_{n}}{y^{2k+n+q+\alpha+2}}-l (l+1) \sum_{n=0}^\infty \frac{a_{n}}{y^{n+\alpha+2}}=0$$

Where $\alpha$ is an unknown exponent.

Multiplying by $y^{\alpha+2}$, we have:

$$\sum_{n=0}^\infty \frac{(n+\alpha)(n+\alpha+1) a_{n}}{y^{n}}+\sum_{n=0}^\infty \frac{(n+\alpha)(n+\alpha+1) a_{n}}{y^{n+2}}-2\sum_{n=0}^\infty \frac{(n+\alpha) a_{n}}{y^{n}}+ \\ + \frac{q}{b^q} \sum_{n=0}^\infty \sum_{k=0}^\infty \frac{(-1)^k (q/2)_k}{k!} \frac{(n+\alpha) a_{n}}{y^{2k+n+q}}-l (l+1) \sum_{n=0}^\infty \frac{a_{n}}{y^{n}}=0$$

Let's assume $q$ is a positive integer, so $q=1,2,3,\ldots$. Then we can collect the powers of $y$.

$$\sum_{n=0}^\infty \frac{(n+\alpha)(n+\alpha+1) a_{n}}{y^n}+\sum_{n=2}^\infty \frac{(n+\alpha-2)(n+\alpha-1) a_{n-2}}{y^n}-2\sum_{n=0}^\infty \frac{(n+\alpha) a_{n}}{y^n}+ \\ + \frac{q}{b^q} \sum_{k=0}^\infty \sum_{n=2k+q}^\infty \frac{(-1)^k (q/2)_k}{k!} \frac{(n-2k-q+\alpha) a_{n-2k-q}}{y^n}-l (l+1) \sum_{n=0}^\infty \frac{a_{n}}{y^n}=0$$

Since $q>0$, it's clear that the indical equation reads:



So we have:

$$\alpha_{1,2}= \frac{1}{2} \pm \sqrt{l(l+1)+\frac{1}{4}}$$

The recurrence relation in general should probably look like this (check for a few values of $q$ and $n$ though, because I may have made a mistake in collecting the terms):

$$ \left((n+\alpha-1)(n+\alpha)-\alpha(\alpha-1) \right) a_{n}+(n+\alpha-2)(n+\alpha-1) a_{n-2} + \\ + \frac{q}{b^q} \sum_{k=0}^{\lfloor \frac{n+q}{2} \rfloor} \frac{(-1)^k (q/2)_k}{k!} (n-2k-q+\alpha) a_{n-2k-q} =0$$

Where we obviously take $a_{-1}=a_{-2}=a_{-3}= \dots=0$.

I have replaced $l(l+1)$ by $\alpha(\alpha-1)$, which makes the expression work for the both roots of the indical equation.

For $q$ not an integer, I'm not sure what to do.

  • $\begingroup$ Thanks Yuriy. I think i need to check this out. I'll get back to you. $\endgroup$ – user583893 Aug 5 at 14:01
  • $\begingroup$ Hi @Yuriy S. How do I make sense with a recurrence relation containing three coefficients? $\endgroup$ – user583893 Aug 11 at 11:44

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.